PENGARUH CORPORATE SOCIAL RESPONSIBILITY, CORPORATE GOVERNANCE, DAN FIRM AGE TERHADAP FIRM PERFORMANCE - Joan Adesaputra; Yanti Yanti (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
The purpose of this research is to empirically examine the influence of corporate social responsibility, corporate governance and firm age toward firm performance measured with Return on Assets (ROA). Corporate social responsibility measured by Global Reporting Initiative (GRI) index, corporate governance measured by board size and independent boards, and firm age measured by the number of years the company has been established. This research uses purposive sampling method with a total sample of 62 companies listed on the Indonesia Stock Exchange in 2017-2019 periods. The results of this study indicate that corporate social responsibility and board size have no significant effect on firm performance. Independent boards and firm age have positive and significant effect on firm performance.